2020
DOI: 10.1108/jabs-06-2018-0168
|View full text |Cite
|
Sign up to set email alerts
|

The effect of service innovation on customer behavioral intention in the Taiwanese insurance sector: the role of word of mouth and corporate social responsibility

Abstract: Purpose Service innovation has been one of the essential elements to meet the customers’ requirements, but few studies discuss service innovation regarding behavioral intention in the insurance industry. This paper aims to investigate the effects of service innovation on customer behavioral intention and examines the role of word-of-mouth (WOM) and corporate social responsibility (CSR). Design/methodology/approach This paper used a survey to assess consumer behavioral intention regarding service innovation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 85 publications
3
33
0
Order By: Relevance
“…H1 has a path of -0.216 while H3 has 0.263 and H5 has the greatest contribution to the intention of use with 0.673. We can also verify that the greatest contribution to the intention to use is made by word of mouth [83].…”
Section: Discussionmentioning
confidence: 76%
“…H1 has a path of -0.216 while H3 has 0.263 and H5 has the greatest contribution to the intention of use with 0.673. We can also verify that the greatest contribution to the intention to use is made by word of mouth [83].…”
Section: Discussionmentioning
confidence: 76%
“…Research on this subject, however, remains immature (Tajeddini et al, 2020;Ardito et al, 2017) and empirical studies focusing on this subject remain scarce (Bonfanti et al, 2018;Losey, 2012) in the government sector in particular (AlMarzouqi, 2019;Battistelli et al, 2014). Studies have stressed the need for such organizations to investigate this relationship (Stojcic et al, 2020;Carmeli and Schaubroeck, 2013), given the lack of academic attention (Chang and Lee, 2020) and the weak interest of government organizations in this subject (Carmeli and Schaubroeck, 2013). In addition, studies have suggested conducting research on service innovation in various countries and different service industries (Bonfanti et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some writers approached it from the point of view of market development systems, while others addressed it from the perspective of resource growth and culture (Chang and Lee, 2020;Booyens and Rogerson, 2016). It was presented by some from positive and interactive perspectives (Akbari and Monzavi, 2015).…”
Section: Service Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies in the field of life insurance; however, only few studies have been conducted so far in the field of life insurance pertaining to CSR. Through their paper in the context of the Taiwanese insurance business, Chang and Lee (2020) revealed that CSR has a moderating effect on the relationship between service innovation and behavioural intentions. Through their article, Lee et al (2017) reported that CSR has a significant positive effect on corporate reputation and customer loyalty in the non-life insurance business.…”
Section: Literature Reviewmentioning
confidence: 99%